Myosteatosis to predict inferior perioperative outcome in patients undergoing orthotopic liver transplantation. Issue 2 (18th September 2019) - Czigany, Zoltan; Kramp, Wiebke; Bednarsch, Jan; van der Kroft, Gregory; Boecker, Joerg; Strnad, Pavel; Zimmermann, Markus; Koek, Ger; Neumann, Ulf Peter; Lurje, Georg
Abstract : Muscle wasting and alterations of body composition are linked to clinical outcomes in numerous medical conditions. The role of myosteatosis in posttransplant outcomes remains to be determined. Here we investigated skeletal muscle mass and myosteatosis as prognostic factors in patients undergoing orthotopic liver transplantation (OLT). The data of 225 consecutive OLT recipients from a prospective database were retrospectively analyzed (May 2010‐December 2017). Computed tomography–based skeletal‐muscle‐index (muscle mass), visceral‐fat‐area (visceral adiposity), and mean skeletal‐muscle‐radiation‐attenuation (myosteatosis) were calculated using a segmentation tool. Cut‐off values of myosteatosis resulted in a good stratification of patients into low‐ and high‐risk groups in terms of morbidity (Clavien‐Dindo ≥3b). Patients with myosteatosis had significantly higher complication rates (90‐day Comprehensive Complication Index 68 ± 32 vs 44 ± 30, P < .001) and also displayed significantly longer intensive care (18 ± 25 vs 11 ± 21 days, P < .001) and hospital stay (56 ± 55 vs 33 ± 24 days, P < .001). Estimated costs were 44% higher compared to patients without myosteatosis. Multivariable analysis identified myosteatosis as an independent prognostic factor for major morbidity (odds ratio: 2.772, confidence interval: 1.516‐5.066, P = .001). Adding myosteatosis to the well‐established Balance‐of‐Risk‐(BAR) score resulted in an increased prognostic value compared to the original BAR score. Myosteatosis may be a useful parameter to predict perioperative outcome in patients undergoing OLT, supporting the role of muscle quality (myosteatosis) over quantity (muscle mass) in this setting. Abstract : This study demonstrates the association of myosteatosis with inferior perioperative outcome in patients undergoing orthotopic liver transplantation, supporting the role of muscle quality (myosteatosis) over quantity (muscle mass) in this setting.